"Right in the Middle": An Experience of Women Reconciliation within the D.I.Y. Movement. Issue 1 (October 2015) - MORENO, ANDREA MORALES
Abstract : A very personal view of how a Mexican teenager finds empowerment in the D.I.Y. punk culture and how she manages to reinterpret her feminity in a patriarchal country by making meaningful creations for her and other girls.